Design of Assistive Device For Blind People Based on Arduino Nano With Global Positioning System (GPS) Tracker - Sobari, Muhammad; Putri, Fairuz Antoni; Toha, Agung Muhamad; Wulandari, Rindi (LPPM Universitas Andalas, 2024)
There are many people who do not have the ability to see so they have difficulty in carrying out activities. They need the help of others to carry out their daily activities. Therefore, the purpose of this research is to create a blind assistive device based on arduino nano with Global Positioning System (GPS) tracker in order to help blind people carry out activities independently. The method used in this research is experimental method. Based on the test results, this tool is able to detect objects from the front, left, and right at a distance of 100 cm then provide voice instructions through the speaker, and this tool can send the location of its users to certain people through the GSM module (Global System for Mobile Communication). Based on the comparison of location readings between the GPS module and google maps, the location read by the GPS module can be said to be quite accurate. From the distance measurement average error value of 0-2%, so the accuracy level of the system is 98%. The performance constraints of this tool are when conditions in the room GPS module and GSM module are difficult to get a signal because it is blocked by the room.